"I have to be a man for my son": The narrative uses of fatherhood in prison. (January 2023) - Schultz, William J; Bucerius, Sandra M; Haggerty, Kevin D
Research on incarcerated fathers tends to accentuate the harmful familial consequences of parental incarceration and discuss how having children might prompt incarcerated fathers to desist from crime. Less attention has focused on how narratives of fatherhood shape the day-to-day dynamics of incarceration. Drawing on 93 qualitative interviews with incarcerated fathers in Western Canada, we focus specifically on our participants' parenting narratives. Such narratives are significant interventions in the world, allowing incarcerated fathers to frame their identities in particular ways while simultaneously shaping personal behaviour. Our research, 1. Identifies important fatherhood narratives provided by our participants, and 2. Details how such narratives operate in prison, allowing our participants to advance personal agendas that are themselves related to the dynamics of incarceration. In doing so, we provide insights into incarcerated fathers' situations and advance criminological efforts to appreciate how different actors entangled in the criminal justice system conceive, manage, and narrate their situation.